Wellbeing Outcomes of Lower Income Renters: A Multi-level Analysis of Area Effects - Parkinson, S.; Melek, C.; Ong, Rachel; Taylor, E. (Australian Housing and Urban Research Institute (AHURI), 2013)
The purpose of this Positioning Paper is to outline the conceptual and methodological framework that will guide the empirical analysis across all stages of the research. It also presents our sample framework for identifying lower income renters and a preliminary descriptive and area-based analysis of their circumstances drawing on 10 years of HILDA data and the 2011 Census.